2019
DOI: 10.5465/amle.2017.0389
|View full text |Cite
|
Sign up to set email alerts
|

Choices and Consequences: Impact of Mobility on Research-Career Capital and Promotion in Business Schools

Abstract: We focus on the role that domestic and international mobility play in achieving a business academic's career outcomes. We seek to advance existing research by taking a morenuanced approach to the study of mobility. Using a sample of 376 tenured faculty members from 20 highly research-visible European business schools in 10 countries, we explore different patterns of mobility and highlight their link to research-career capital and the speed of academic promotion. Our findings show that mobility has a positive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 106 publications
1
11
0
Order By: Relevance
“…publications) [10] or mobility events (i.e. international moves) [11]. Following Abbott, we view the career pattern itself as an outcome [12].…”
Section: Introductionmentioning
confidence: 99%
“…publications) [10] or mobility events (i.e. international moves) [11]. Following Abbott, we view the career pattern itself as an outcome [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, Bozeman and Gaughan (2011) found no evidence that men or women adopt a "nationalist" strategy (wishing collaborators from one's own nation or shared language) in collaboration. Prior studies have shown that women are less likely to have international mobility (El-Ouahi et al, 2021;Jöns, 2011;Leemann, 2010;Ryazanova & McNamara, 2019). This varies by many factors such as discipline, career stage and country of origin.…”
Section: Mobility and Gendermentioning
confidence: 99%
“…However, Bauder (2020) reports that mobility can lead to the loss of national social capital that negatively affects early-career researchers in particular. Furthermore, the results of a study by Ryazanova and McNamara (2019) indicate a negative effect of international mobility at the first postdoctoral researcher (postdoc) job on research productivity, however they found that an international movement between year 2 and 7 of a postdoc is better than later.…”
Section: Mobility and Academic Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…We also note that amongst the current cohort of business school academics, women tend to be less globally mobile than their male counterparts. It has been suggested that this is for reasons related to personal life (caring responsibilities) rather than lack of awareness about the professional benefits of mobility, and, even when women have moved internationally previously, they may be reluctant to do so again because of unsettling their families (Ryazanova & McNamara, 2019). Table 1 includes a summary of biodata for the interviewees.…”
Section: Data Collection Proceduresmentioning
confidence: 99%